Criminal protection for minors in terms of social - Darwish, Kolagen; Dawoud, Sabah (Journal of Legal Sciences, 2023)
Minors are considered the category that cannot and does not have the right to protect themselves or obtain their rights, and hence it was necessary to protect and take care of them. The care of minors in its natural form is based on his care within his family and society in general in which he grows up and interacts with his members. Hence, we find the criminal legislator has punished for the actions that It affects the social position of the minor, and for the purpose of explaining the objective criminal protection of the minor from the social point of view, we divided this topic into two sections.